2003
DOI: 10.1073/pnas.0830026100
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of high-affinity insulin receptor agonists and antagonists from peptide building blocks

Abstract: Insulin is thought to elicit its effects by crosslinking the two extracellular ␣-subunits of its receptor, thereby inducing a conformational change in the receptor, which activates the intracellular tyrosine kinase signaling cascade. Previously we identified a series of peptides binding to two discrete hotspots on the insulin receptor. Here we show that covalent linkage of such peptides into homodimers or heterodimers results in insulin agonists or antagonists, depending on how the peptides are linked. An opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 11 publications
4
84
1
Order By: Relevance
“…Therefore the difference in mitogenitic response between s597 and insulin results from different signaling more than from cross-talking with IGF-1R. This is supported by the finding that s597 had no effect on phosphorylation of the IGF-1R, ERK1/2 or PKB in untransfected L6 cells [6] and by studies of the gene expression profile in IRtransfected L6 myoblasts after IR activation by insulin and s597, using microarray technology [7]. It was shown that almost half of the genes differentially regulated by s597 and insulin were related with cell proliferation and growth.…”
Section: Introductionsupporting
confidence: 57%
“…Therefore the difference in mitogenitic response between s597 and insulin results from different signaling more than from cross-talking with IGF-1R. This is supported by the finding that s597 had no effect on phosphorylation of the IGF-1R, ERK1/2 or PKB in untransfected L6 cells [6] and by studies of the gene expression profile in IRtransfected L6 myoblasts after IR activation by insulin and s597, using microarray technology [7]. It was shown that almost half of the genes differentially regulated by s597 and insulin were related with cell proliferation and growth.…”
Section: Introductionsupporting
confidence: 57%
“…3,4 Furthermore we have earlier published on other peptides that bind to the insulin receptor with regard to affinity for the receptor and ability to stimulate lipogenesis in mouse adipocytes (8,9), but intracellular signaling was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently homodimers and heterodimers of the site 1 and 2 peptides have been generated. Many of these can activate the insulin receptor with high potency and specificity, possibly through a mechanism similar to the binding of insulin (9). One of these peptides was furthermore found to lower the blood glucose level in rats with equipotency to insulin.…”
mentioning
confidence: 99%
“…These studies prompted the idea that blocking the insulin receptor with a small molecule or peptide antagonist could recapitulate these effects, including the induction of β-cell replication. In fact, treatment with one such insulin receptor antagonist, a novel peptide named S961, results in hyperinsulinemia in rats (Schäffer et al, 2003;Schäffer et al, 2008;Vikram and Jena, 2010).…”
Section: Identifying Mechanisms Of Replication Induction Using the LImentioning
confidence: 99%
“…These studies prompted the idea that blocking the insulin receptor with a small molecule or peptide antagonist could recapitulate these effects, including the induction of β-cell replication. In fact, treatment with one such insulin receptor antagonist, a novel peptide named S961, results in hyperinsulinemia in rats (Schäffer et al, 2003;Schäffer et al, 2008;Vikram and Jena, 2010).Furthermore, an additional study of the LIRKO model revealed that β-cells were specifically induced to replicate in this context with no effect on α-cells or other non-pancreatic tissues (El DEVELOPMENT 2480 Ouaamari et al, 2013). This study also demonstrated that the induced replication could occur in a normal parabiotic partner (with normal blood glucose and insulin levels) if that animal was joined with a LIRKO mouse partner, suggesting both that a systemic factor was at work and that it could work independently of blood glucose levels.…”
mentioning
confidence: 99%